2016
DOI: 10.7860/jcdr/2016/22332.9051
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction and Internal Fixation of Displaced Calcaneum, Intra-Articular Fractures by Locking Calcaneal Plate

Abstract: Open reduction and internal fixation of intra-articular fractures of the calcaneum with locking calcaneal plate gives good results. Maintenance of calcaneal height and Bohler's angle helps to decrease the incidence of subtalar arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…One study reported that one-third of patients in the hollow-screw xation group had poor long-term functional outcomes [24],Some literatures reported that the nal functional outcome of most patients in the plate group was good [25,26].Our results showed no signi cant difference in nal AOFAS and VAS scores between the plate combined with screws and the plate group, suggesting that the two surgical methods for calcaneal fracture are similar in ankle function.…”
Section: Discussionmentioning
confidence: 42%
“…One study reported that one-third of patients in the hollow-screw xation group had poor long-term functional outcomes [24],Some literatures reported that the nal functional outcome of most patients in the plate group was good [25,26].Our results showed no signi cant difference in nal AOFAS and VAS scores between the plate combined with screws and the plate group, suggesting that the two surgical methods for calcaneal fracture are similar in ankle function.…”
Section: Discussionmentioning
confidence: 42%